(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
This article discusses the role of digital technologies in teaching creative thinking to students in higher education. Analysis of the features of the use of effective digital technologies in the teaching of computer science, teaching technologies, determining the role and importance of effective digital technologies in the educational process in higher education, the practice of using digital technologies, digital in education development of proposals and recommendations for methodological improvement of technology use.